The logic of delegation and institutional contexts: Ministerial selection under mixed-member systems in Japan. Issue 4 (December 2019) - Kubo, Hiroki
How do electoral systems and legislative institutions modify the logic of delegation in ministerial selection processes? This study argues that candidate-centered electoral systems and bicameralism increase the risk of agency loss. I reveal how these two institutional contexts mediate party leaders' strategies on the allocation of ministerial posts by analyzing Japan's ministerial-selection data and survey-based ideal point estimates from 2003 to 2014. The empirical results indicate that, under the party-centered electoral systems of the lower house, individuals' ideological proximity to the party leadership increases the probability of their joining a cabinet. However, party leaders allocate cabinet posts to ideological outliers in the upper house and also select MPs who are ideologically distant from the party leadership under the candidate-centered electoral systems in order to maintain party unity.